Mengubah Limbah Kayu Menjadi Produk Bernilai Tinggi di Industri Kreatif - Nughthoh Arfawi Kurdhi; Saputro, Dewi Retno Sari; Widyaningsih, Purnami; Sutanto, Sutanto; Setiyowati, Ririn; Sudibyo, Nugroho Arif (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The UMKM involved in this community partnership program is engaged in the production of teak wood furniture. The issues currently faced are (1) a limited range of furniture products and (2) traditional management and marketing methods. This study aimed to implement technological induction to enhance productivity, creativity, and competitiveness within these UMKMs. The technological induction involved providing modern production tools for creating innovative products and developing an application boot program and server computer to enhance marketing efforts. A mixed-methods approach was used, combining case study observations and user-centred design principles to create technological solutions. The program's outcomes were assessed through partner training and mentoring, employing a problem-solving approach to address post-implementation challenges. The study found that introducing advanced production tools and digital marketing strategies significantly increased the variety of products, streamlined production processes, and expanded market reach, positioning the UMKMs for improved competitiveness in the national market. This research underscores the importance of integrating technology into small-scale industries for sustainable growth. Future efforts should focus on scaling these practices to other creative sectors for broader economic impact.